Integrating Ontologies with Multi-Agent Systems through CArtAgO Artifacts - Freitas, Artur; Panisson, Alison R.; Hilgert, Lucas; Meneguzzi, Felipe; Vieira, Renata; Bordini, Rafael H. (2015 IEEE/WIC/ACM International Conference on Web Intelligence and Intelligent Agent Technology (WI-IAT), 2015)
Several advantages can be obtained by allowing multi-agent systems to easily access ontologies, for example, in scenarios where agents make their decisions based on the knowledge provided by ontologies. Thus, this paper presents an infrastructure to allow the use of web ontologies in different agent-oriented platforms. The agents use this infrastructure layer as a tool for storing, accessing and querying domain-specific OWL ontologies. As a result, this layer allows an integration of agent platforms with semantic web data and ontologies. We exemplify in practice how agents, coded in one such platform, can use the proposed access layer to ontological reasoning engines, as well as which features can be obtained from it. The performance of this semantic infrastructure is evaluated and compared against usual knowledge representation in agent programming.